A STUDY ON THE EFFECT OF METHANOLIC EXTRACTS OF Maranta arundinacea LEAVES AGAINST URINARY TRACT INFECTION CAUSING PATHOGENS - ASWINI, B.; SIVAGURUNATHAN, P.; SOWNDARYA, S.; SUMATHI, V.; VIVEKANANDHAN, S.; UMA, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Urinary Tract Infection (UTI) has become a major socio-economic burden because of the multi-drug resistance and the high frequency of repeated use. The goal of the research paper is to describe the use of natural therapies in the treatment and management of UTIs. Even if conventional medicine is less effective than herbal remedies, further research is needed to understand the phytoconstituents and their mechanisms of action that are responsible for the treatment and management of UTI. Many therapeutic benefits, including antibacterial activity, are attributed to Maranta arundinacea. Therefore, commonly known UTI pathogens like Staphylococcus aureus, Bacillus sublitis, Enterococcus sp., Salmonella paratyphi, Pseudomonas aeroginosa, Proteus mirabilis, Escherichia coli, Klebsiella pneumonia, Salmonella typhi, and Enterobacter sps. were evaluated by phytochemical analysis and in vitro antimicrobial activity of this plant The antibacterial activity was studied by dilution and diffusion assays. The results of this study conclude that arrowroot methanolic extract can inhibit the growth of pathogens causing UTI with the most effective concentration is 80 µg/ml.